Epoxy-reinforced heavy metal oxides for gamma ray shielding purposes - Almuqrin Aljawhara H.; Aloraini Dalal Abdullah; Abualsayed Mohammad Ibrahim (Open Chemistry, 2023)
Epoxy resins with varying amounts of MoO3 were theoretically investigated for their radiation shielding ability at low energies (between 0.0395 and 0.344 MeV). The quantity of MoO3 varied from 0 to 30%, and relevant shielding parameters were obtained and analyzed from Phy-X software. The half value layer (HVL) of the resins demonstrated that increasing MoO3 content improved the space-efficiency of the prepared samples at all tested energies, leading to the Mo4 sample, the epoxy resin with the greatest MoO3 content having the smallest HVL. Additionally, the mean free path of the materials has an inverse relationship with their density, which increased with additional MoO3. The tenth value layer ratio between Mo1 and Mo4 illustrated how the introduction of Mo has a much greater effect on thickness reduction at lower energies than at higher energies due to photoelectric phenomena. The Z eff and N eff parameters showed how the epoxy samples benefitted from the introduction of MoO3 at different energies.